Characteristics and predictors of progression in an Egyptian multiple sclerosis cohort: a multicenter registry study - Hamdy SM (Dove Medical Press, 2017)
Sherif M Hamdy,1 Maged Abdel-Naseer,1 Nevin M Shalaby,1 Alaa N Elmazny,1 Ahmed A Nemr,2 Amr Hassan,1 Mohamed I Hegazy,1 Husam S Mourad,1 Nirmeen A Kishk,1 Mona A Nada,1 Ahmed Abdelalim,1 Amr M Fouad,1 Hatem S Shehata1 1Neurology Department, Cairo University, 2Neurology Department, Maadi Military Hospital, Cairo, Egypt Background: Multiple sclerosis (MS) is a complex autoimmune disease with a heterogeneous presentation and diverse disease course. Recent studies indicate a rising prevalence of MS in the Middle East.Objective: To characterize the demographics and disease features of Egyptian patients attending four tertiary referral MS centers in Cairo.Materials and methods: This was a retrospective, observational study on 1,581 patients between 2001 and 2015. Medical records were reviewed and data were identified and extracted in a standardized electronic registry.Results: The mean age of disease onset was 26.6±7.8 years, with the majority being female (2.11:1). Relapsing–remitting MS was the most common type (75.1%). The main presenting symptom was motor weakness (43.9%), which was also the most frequent symptom during the disease course. Family history of MS was found in 2.28%. Higher initial Expanded Disability Status Scale score, black holes, and infratentorial lesions on initial magnetic resonance imaging were independent factors for disease progression by univariate analysis (OR 3.87 [95% CI 1.84–6.51], 4.14 [95% CI 3.08–5.58], 4.07 [95% CI 3.21–4.99], respectively); however, in multivariate analysis, only infratentorial lesions were an independent risk for disease progression (OR 6, 95% CI 2.99–12.02; P=0.0005).Conclusion: The results from this registry – the largest for MS in the Arab region to date – are comparable to other registries with slight differences. Keywords: multiple sclerosis, MS registry, epidemiology, Middle East, North Africa, Egypt